2017
DOI: 10.5267/j.ac.2016.8.001
|View full text |Cite
|
Sign up to set email alerts
|

Trade credit and bank loan in period of financial crisis: Evidence from Tunisian exporting companies

Abstract: This paper examines the relationship between trade credit and bank loan during the financial crisis using annual data on Tunisian exporting companies over the period [2005][2006][2007][2008][2009][2010][2011]. Results based on 2SLS regression have shown that trade credit and bank credit were simultaneously determined and maintained a complementary effect before 2008 financial crisis. On the other side, the substitution effect has been detected between the two sources of short term financing during 2008 financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It showed that financially constrained firms used trade credit as another financing source during financial crisis. Bellouma [17] (the case of Tunisian firms) found out the substitute effect between trade credit and bank credit, and confirmed that during the financial crisis firms relied more on trade credit. Ellingsen, Jacobson and Schedvin [18] revealed that clients preferred trade credit over other available funding sources.…”
Section: Empirical Evidence Of Previous Studiesmentioning
confidence: 60%
“…It showed that financially constrained firms used trade credit as another financing source during financial crisis. Bellouma [17] (the case of Tunisian firms) found out the substitute effect between trade credit and bank credit, and confirmed that during the financial crisis firms relied more on trade credit. Ellingsen, Jacobson and Schedvin [18] revealed that clients preferred trade credit over other available funding sources.…”
Section: Empirical Evidence Of Previous Studiesmentioning
confidence: 60%
“…Concerning working capital management manufacturing companies should manage their trade activities at a minimum cost. Analysing credit worthiness for new and existing customers makes firms eliminate extra cost of using external resources such as credit agencies (Bellouma, 2014). Manufacturing firms should ensure that customers pay their bills on time thus reducing costs of hiring debt collectors and debts write off (Dary & James, 2019).…”
Section: Transaction Cost Theorymentioning
confidence: 99%
“…Garcia-Appendini and Montoriol-Garriga (2013) demonstrate that firms with high pre-crisis liquidity levels provide more trade credit. Moreover, Bellouma (2013) shows that during the financial crisis, firms relied more on trade credit.…”
Section: Literature Reviewmentioning
confidence: 99%